THE FINLAND EDUCATION SYSTEM. - G’aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2023)
This article provides information about the structure of the Finland education system, its achievements, as well as the specific characteristics of studying in Finland schools, their types, and the reforms that are being carried out in this system in our country.